Green supply chain management: the development of supply chain carbon maps. (1st January 2012) - Acquaye, Adolf A.; Barratt, Paul; Topi, Corrado; Glew, David; Kuylenstierna, Johan; Koh, S.C. Lenny; Barrett, John; McQueen-Mason, Simon
In recent times, environmental thinking has become a prominent feature in the design of supply chain networks leading to the concepts of low carbon supply chains and green supply chain management. Understanding the sources and levels of emissions within the supply chain is the first step needed to fully design a low carbon supply chain. This paper helps to develop the concept of supply chain carbon map which provides a visual representation of the sources, levels of emissions and hotspots at a whole supply chain level. This is developed within an extended system framework using the hybrid lifecycle assessment methodology to generate carbon emissions for a mono crystalline silicon PV system and using a multi-regional input-output model to ensure system boundary completeness. The paper also discusses how the development of a whole supply chain perspective of carbon maps ensures that collaborative supply chain networks of firms can be mapped hence firms can gain a better understanding of their supply chain impacts and therefore help its sustainable management.